2021
DOI: 10.1111/bcpt.13575
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous adipose tissue composition and function are unaffected by liraglutide‐induced weight loss in adults with type 1 diabetes

Abstract: Adipose tissue is the primary energy reservoir of the human body, which also possesses endocrine functions. The glucagon‐like peptide agonist liraglutide produces weight loss, although the specific effects on adipose tissue are unknown. We aimed to characterize the white adipose tissue composition and pericellular fibrosis of subcutaneous adipose tissue in response to liraglutide treatment. Furthermore, we explored the level of circulating free fatty acids, cluster of differentiation 163 (CD163) macrophage mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(90 reference statements)
1
2
0
Order By: Relevance
“…Darabian et al, and Momesso et al reported close to our results concerning the accumulation of visceral fat tissue in patients with T1DM [5,12]. Wegeberg et al reported lack of reduction of subcutaneous fat tissue in patients with T1DM [17].…”
Section: Discussionsupporting
confidence: 89%
“…Darabian et al, and Momesso et al reported close to our results concerning the accumulation of visceral fat tissue in patients with T1DM [5,12]. Wegeberg et al reported lack of reduction of subcutaneous fat tissue in patients with T1DM [17].…”
Section: Discussionsupporting
confidence: 89%
“…Of those, 45 were finally deemed eligible for inclusion in the systematic review. The studies by Camastra et al 2017, 16 Jendle et al 2009, 17 Bays et al 2017, 18 Blundell et al 2017, 19 Koska et al 2018, 20 Basolo et al 2018, 21 Cusi et al 2018, 22 Newsome et al 2021, 23 Wegeberg et al 2021, 24 Blonde et al 2021, 25 and Flint et al 2020 26 were not further used for the meta‐analysis due to lack of appropriate extractable data of interest. Consequently, 34 studies were included in the effect estimate models.…”
Section: Resultsmentioning
confidence: 99%
“…In the condition of long-term hyperglycemia, the body of T2DM patients gradually presents inflammatory responses, and most diabetic patients also have dyslipidemia, which destroys vascular endothelial function of patients [16]. However, vascular endothelial function impairment is the basic pathological change of various complications in T2DM patients, which will lead to atherosclerosis and thrombosis [17].…”
Section: Groupsmentioning
confidence: 99%